2015
DOI: 10.4172/2167-7700.1000160
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Epithelioid Hemangioendothelioma: Advances in Treatment Options despite a Rare Vascular Tumor

Abstract: IntroductionWe have already discussed about dail and liebow describing pulmonary epithelioid hemangioendothelioma (PEH) as an aggressive bronchoalveolar cell carcinoma with a remarkable propensity to invade adjacent blood vessels and small airways, the following Weiss and Enzinger description of epithelioid hemangioendothelioma (EHE) as a vascular bone and soft tissues tumor showing intermediate malignancy between hemangioma and angiosarcoma, and the final confirmation from Weldon-Linne of a factor-VIII-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…There is no established standard treatment consensus for therapeutic regimens available, particularly owing to its borderline malignancy features and scarcity of cases [ 30 , 79 ]. Spontaneous partial regressions are reported, particularly in asymptomatic patients, as we already reported [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no established standard treatment consensus for therapeutic regimens available, particularly owing to its borderline malignancy features and scarcity of cases [ 30 , 79 ]. Spontaneous partial regressions are reported, particularly in asymptomatic patients, as we already reported [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pinet et al [ 82 ] reported a case of an aggressive form of pleural EH resulting in complete remission after treatment with carboplatin plus etoposide. Given the vascular origin of this tumor, the use of antiangiogenetic drugs reasonably might achieve good outcomes, including thalidomide, lenalidomide, and bevacizumab [ 61 , 79 , 84 86 ]. Ye et al [ 58 ], in their review concerning chemotherapy and immunotherapy used in PEH, demonstrated a good partial response to chemotherapy with carboplatin, paclitaxel, bevacizumab, thalidomide, and α -interferon.…”
Section: Discussionmentioning
confidence: 99%